Tau theory based path planning for quadrotors - Tan, Hong Tak (2016)
The title of this project is ‘Tau Theory Based Path Planning for Quadrotors’. The quadcopter is one of the Unmanned Aerial Vehicles (UAVs). The UAVs are aircraft without pilot onboard, also known as the drone. It is important to plan the paths for the UAVs in order to fly smoothly and safely. There are many strategies proposed by the researchers, ‘intrinsic tau gravity guidance theory’ is one of them and this theory is the focus of this project. Ecological intrinsic tau gravity guidance theory has been first proposed by David Lee. In addition, Farid Kendoul continues to research the effectiveness of applying this theory. He applies the theory to move and guide the UAVs with four dimensions (three spatial dimensions plus one time controls). The purpose of intrinsic tau gravity guidance theory is to achieve a smooth perching with nonzero initial velocity and control the required time to complete the trajectories. The objectives of this project are to design the trajectories for the UAV and improve the performance of the UAV. Different program codes of the trajectories are presented in this report. The trajectories include x-directional trajectory, circular trajectory, two-dimensional curvature trajectory with intrinsic coupling, three-dimensional curvature trajectory with intrinsic coupling and three-dimensional intrinsic coupling trajectory with trap fuzzy as well as three-dimensional intrinsic coupling trajectory with gauss fuzzy. The equations of the intrinsic tau theory were applied in the trajectories in order to improve the performance of the UAV. The explanation of the program codes of the trajectories also presented in this report. The experiments were carried out with the device of VICON Motion Capture System in order to test the trajectories of the UAV. The experiments were conducted fifteen times each and the results of the experiments were processed with MATLAB software. The results were analyzed and the coding was modified according to the data analysis. The results of the experiments were plotted as figures and presented in this report. Besides the results of the experiments, the comments of the result and the idea of the improvement plan were presented also. In the end of the report, the conclusion was made and the future works of the project were mentioned.